2016
DOI: 10.1007/s11427-016-5050-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dengue virus replication by diisopropyl chrysin-7-yl phosphate

Abstract: Dengue fever is a tropical disease and caused by dengue virus (DENV), which is transmitted by mosquitoes and infects about 400 million people annually. With the development of international trade and travel, China is facing a growing threat. Over 40 thousands of people were infected during the 2014 DENV outbreak in Guangdong. Neither licensed vaccine nor therapeutic drug has been available. In this report, we isolated two clinical DENV strains. The full-length genome was sequenced and characterized. We also ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The compound at 10 µM was introduced into the virus-infected cells based on the efficacy and cytotoxicity profile. According to previous reports, viral translation is a primary target during early infection [9,12,17]. The compound is located at the perinuclear region and colocalized with a dengue protein for 1-6 h after infection (Figure 3B).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The compound at 10 µM was introduced into the virus-infected cells based on the efficacy and cytotoxicity profile. According to previous reports, viral translation is a primary target during early infection [9,12,17]. The compound is located at the perinuclear region and colocalized with a dengue protein for 1-6 h after infection (Figure 3B).…”
Section: Discussionsupporting
confidence: 75%
“…Apigenin was chosen as a flavone derivative because its existing hydroxyl group on the B-ring was suitable for a terminal alkyne modification. Although apigenin itself was a moderately potent inhibitor at the EC 50 of 10.55 ± 3.37 µM, it represented its chemical relatives like chrysins and baicaleins (Figure 1A), which were strong DENV inhibitors [9,12,17] but lacked the B-ring hydroxyl group for alkyne addition. The newly synthesized alkyne-tagged apigenin identity was verified by 1 H-NMR, and 13 C-NMR (Figures S2-S7 in Supplementary Materials).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Du et al (2016) demonstrated the antiviral activity of a chrysin analog, a phosphate ester substituted at position 7 by a diisopropyl phosphate group, against DENV1 and DENV2. The phosphorylated analog inhibited viral protein synthesis in cells infected with DENV1 and DENV2, with IC 50 values of 18.6 and 15.1 μmol L −1 , respectively, demonstrating efficacy against the replication of these two serotypes in cell culture without detectable cytotoxicity (Du et al, 2016). Chen et al (2004) demonstrated that phosphorylated flavonoids have strong binding affinities in addition to forming noncovalent complexes with many proteins more easily than nonphosphorylated compounds (Chen et al, 2004).…”
Section: Structure: Activity Relationshipmentioning
confidence: 99%
“…Natural compounds derived from plants have been investigated as antiviral agents against DENV. For example, quercetin, naringenin, catechin, and chrysin are flavonoids extracted from plants and were reported to have anti-dengue activity 7 9 . Silymarin, a plant-derived flavonoid extracted from milk thistle, was reported to be a promising antiviral candidate against chikungunya virus (CHIKV) by reducing the viral replication and down-regulation of viral proteins, nsP1, nsP3, and E2E1 10 .…”
Section: Introductionmentioning
confidence: 99%